Bridging Traditional and Digital Learning: The Role of Google Sites in Project-Based Learning at MI Miftahul Huda Selok Anyar Pasirian - Sholeh, Muhammad; Mashudi; Saihan (Program Studi PGMI, 2025)
The integration of information and communication technology (ICT) in education has become increasingly crucial in the 21st century. Project-Based Learning (PjBL) is a relevant learning model that fosters student engagement, creativity, and problem-solving skills. This study analyzes the need for developing Google Sites-based PjBL media at MI Miftahul Huda Selok Anyar Pasirian , where traditional learning methods still dominate, limiting student participation and interaction. Data were collected through observations, questionnaires, interviews, and document analysis, using a qualitative case study approach. The findings indicate that while teachers and students recognize the benefits of digital learning, major challenges such as limited infrastructure, inadequate digital literacy, and unstable internet access hinder effective implementation. The study also reveals a significant gap between national education policies advocating for digital integration and actual classroom practices. Despite these challenges, there is strong interest in adopting Google Sites for PjBL, provided adequate training and institutional support are available. This research contributes to the development of interactive digital learning media that can enhance student engagement and facilitate PjBL implementation. The findings emphasize the importance of structured teacher training, improved digital infrastructure, and stakeholder collaboration to ensure effective technology integration in education. Future research should focus on designing and implementing Google Sites-based PjBL media to optimize learning outcomes.